Pelatihan Pemasaran Budi Daya Jamur Tiram Menuju Pasar Modern dengan Artificial Intelligence (AI) - Akhmad Afandi; Anggreany Hustia; Desy Rahmawati (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2025)
Community service activities carried out in the Ogan Ilir region of South Sumatra aimed to improve the literacy and capacity of business actors, both owners and those involved in oyster mushroom cultivation, in the field of technology-based marketing. These activities were carried out in three integrated sessions during the training. The first session provided an understanding of the basic concepts of oyster mushroom marketing, including an explanation of the differences between traditional and modern markets, as well as an overview of product development strategies aligned with the goal of entering modern markets. The second session focuses on strengthening brand identity and product branding, as well as enhancing the use of e-commerce as an effective distribution tool to reach consumers. The final session involves practical exercises and simulations in the application of artificial intelligence (AI) technology for marketing activities. As a follow-up to the community service activities, in addition to direct implementation, the community service team continues to provide a platform for partners to consult and discuss the distribution of oyster mushrooms, ensuring they are not only utilized by consumers in traditional markets but also distributed in modern markets. Through this initiative, it is hoped that business operators and related parties will be able to design innovative, adaptive, and competitive marketing strategies to enhance the competitiveness of oyster mushroom products in both the national and global markets.